Studies on the Epidemiology of Leaf Rot and Leaf Spot Diseases of Betel Vine (Piper Betle L.) - Huq, MI (Bangladesh Journal of Scientific and Industrial Research, 2012)
The experiment was conducted in an established pan betel vine crop field (Pan boroj). The disease data were recorded for 12 months. The incidence of leaf rot was observed in the month of June, July and August. The peak infection was noted in the second week of August, 2002 when the average temperature, relative humidly and rainfall were 29.60°C, 94.6% and 13.4mm respectively. The incidence of leaf spot was observed during months of March, April and May. But gradually infection reached maximum when average temperature, relative humidly and rainfall parameters were 26.7°C, 88.3% and 19.4mm respectively. The meteorological factor which had greatly influenced initiation of leaf spot was less favourable for leaf rot disease. Key words: Epidemiology; Betel vine; Leaf spot; Leaf rot diseases DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9601 BJSIR 2011; 46(4): 519-522